The SUPDIASI Strategy: Enhancing Teacher Pedagogical Competence Through Technical Guidance - Eka Prasetiawati; Deti Rostini (CV. Media Digital Publikasi Indonesia, 2026)
The pedagogical competence of teachers is a critical determinant of educational quality, yet many educators, particularly at the elementary level, face challenges in designing and implementing effective instruction. This study was prompted by the need for an effective, job-embedded professional development model. This research analyzes the effectiveness of a Technical Guidance (Bimtek) strategy based on the Supervision, Discussion, and Action (SUPDIASI) model in enhancing teacher pedagogical competence. This study employed a qualitative action research methodology conducted at two elementary schools in Cianjur, Indonesia: SDN Sindangsari and SDN Tegalsari. The research was structured around the Plan-Do-Check-Act (PDCA) cycle. Data were collected through a triangulation of methods, including in-depth interviews with teachers and principals, participant observation of the complete SUPDIASI cycle, and analysis of institutional documents such as lesson plans and reflective journals. The findings demonstrate that the SUPDIASI model, managed through a PDCA framework, was highly effective. The initial Plan and diagnostic Supervision revealed specific teacher needs. The collaborative Discussion phase fostered reflective practice and problem-solving. The Action phase led to observable improvements in teachers' use of varied instructional strategies and classroom management. The final Check and Act stages institutionalized a culture of continuous improvement. The Bimtek strategy based on the SUPDIASI model is an effective and replicable framework for enhancing the pedagogical competence of elementary school teachers. By integrating supervision with collaborative reflection and concrete action, this model successfully bridges the gap between theory and practice, fostering a sustainable culture of professional learning.